Peripheral neutrophils and oxidative stress-associated molecules for predicting the severity of asthma: a cross-sectional study based on multidimensional assessment - Mao, Ruolin; Jiang, Zhilong; Min, Zhihui; Wang, Gang; Xie, Min; Gao, Peng; Zhu, Lei; Li, Huayin; Chen, Zhihong (Frontiers in Medicine, 2023)
Objectives: This study aims to explore the relationship between the severity of asthma and neutrophils and related oxidative stress-associated molecules in peripheral blood and induced sputum.Methods: A total of 67 subjects were included in this study, namely, 25 patients with severe asthma and 42 patients with nonsevere asthma. Clinical data, induced sputum and peripheral blood were collected. Lung function and molecules related to oxidative stress in induced sputum and peripheral blood of asthma patients were detected. The relationship between neutrophils and asthma severity was 2 This is a provisional file, not the final typeset article analyzed. HDAC2 mRNA and protein expression levels and HDAC2 activity were also analyzed. Multivariate logistic regression was performed to select statistically significant variables.Results: The absolute value of neutrophils and percentage of neutrophils were higher in the severe asthma patients. These two values were used to predict the severity of asthma by ROC analysis, with the best cutoff values being 4.55×10 9 /L (sensitivity 83.3%, specificity 64.0%) and 55.15% (sensitivity 54.8%, specificity 88.0%). The ROS concentration of neutrophils in the induced sputum samples and the 8-iso-PGF2α concentration in the peripheral blood samples were higher in the severe asthma group (P=0.012; P=0.044), whereas there was reduced HDAC2 protein activity in PBMCs (P<0.001). A logistic equation and a nomogram were created to give a precise prediction of disease severity.Oxidative stress is increased in severe asthma patients. Peripheral blood neutrophils and 8-iso-PGF2α can be used as biomarkers to predict the severity of asthma. A prediction model was created for evaluating asthma severity.